2019
DOI: 10.3121/cmr.2019.1503
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Resistance Patterns in Wisconsin

Abstract: Objective: Surveillance of antimicrobial resistance patterns on a local level can reveal paradigms not obvious on a regional or national scale. Data collection from this perspective may potentially impact local prescribing patterns and empiric treatment guidelines. The objective of this study was to establish a baseline Staphylococcus aureus antibiogram for the state of Wisconsin and to elucidate potential geographic and demographic factors associated with antimicrobial resistance.Design: Multi-center laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Because of the lack of direct involvement in the collection of specimens and because of the utilization of de-identified isolates from routine clinical care, the Surveillance of Wisconsin Organisms for Trends in Antimicrobial Resistance and Epidemiology (SWOTARE) program was not considered to be actively engaged in human subject research by the Marquette University Institutional Review Board. Additional activities relative to the SWOTARE program have been described [18][19][20][21].…”
Section: Clinical Samplesmentioning
confidence: 99%
“…Because of the lack of direct involvement in the collection of specimens and because of the utilization of de-identified isolates from routine clinical care, the Surveillance of Wisconsin Organisms for Trends in Antimicrobial Resistance and Epidemiology (SWOTARE) program was not considered to be actively engaged in human subject research by the Marquette University Institutional Review Board. Additional activities relative to the SWOTARE program have been described [18][19][20][21].…”
Section: Clinical Samplesmentioning
confidence: 99%
“…In a large study from Canada, Adam et al 36 reported that resistance to clindamycin, clarithromycin, and trimethoprim-sulfamethoxazole in the elderly patients was greater when compared with that in adults and children ( P < 0.001 for each antibiotic). Schulte and Munson 50 reported an increased proportion of levofloxacin-resistant S. aureus from patients aged 80 years or older compared with patients aged 0–19 or 40–59 years ( P ≤ 0.046) and an increased percentage of S. aureus resistant to clindamycin (36.3%) compared with 20- to 39-year-old subjects (16.7%, P = 0.026). Similarly, David et al 51 demonstrated increased S. aureus resistance to clindamycin in elderly patients compared with pediatric patients.…”
Section: Methodsmentioning
confidence: 97%
“…Methicillin, a semisynthetic penicillin introduced in 1959, efficiently addressed the penicillin‐resistant strains [10]. MRSA strains carry the mecA gene encoding for PBP2a protein (penicillin‐binding protein 2a) [11]. As per the ICMR annual report 2021, S. aureus did not exhibit complete resistance to vancomycin.…”
Section: Introductionmentioning
confidence: 99%